2017
DOI: 10.1038/gim.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial effects of the Li-Fraumeni Education and Early Detection (LEAD) program on individuals with Li-Fraumeni syndrome

Abstract: Purpose In the past five years new screening protocols have been developed that provide improved cancer screening options for individuals with Li-Fraumeni Syndrome. Very little has been published on the psychosocial impact of these screening protocols. The goals of this study were to determine how participation in screening impacts individuals psychosocially, to examine the benefits and drawbacks of screening, and to evaluate possible barriers to continued screening. Methods We performed a qualitative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 18 publications
2
61
1
Order By: Relevance
“…Overall, the findings suggest that participants comprehended the new risk information and integrated it into existing beliefs about their LS carrier status, including their previous personal and familial experiences of LS. The findings contribute to a small body of emerging research assessing the psychosocial impact of undergoing research-based comprehensive screening for multiple malignancies (Barez, Blasco, Fernandez-Castro, & Viladrich, 2009;McBride et al, 2017;Ross et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Overall, the findings suggest that participants comprehended the new risk information and integrated it into existing beliefs about their LS carrier status, including their previous personal and familial experiences of LS. The findings contribute to a small body of emerging research assessing the psychosocial impact of undergoing research-based comprehensive screening for multiple malignancies (Barez, Blasco, Fernandez-Castro, & Viladrich, 2009;McBride et al, 2017;Ross et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…The availability of research-based screening was significant for men in this study who live with multiple cancer risks as a result of their LS status. The perceived benefits may extend beyond reducing morbidity and mortality to include psychological benefits, such as a source of emotional support and containment for patients (Lammens et al, 2010;McBride et al, 2017;Ross et al, 2017). (Barez et al, 2009;Beckjord, Glinder, Langrock, & Compas, 2009;Benyamini, Nouman, & Alkalay, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that this intensive cancer surveillance protocol has led to the early detection of primary cancers usually only requiring resection instead of chemotherapy and/or radiation, both of which have potential for contributing to treatment related late effects 2 . Once identified early, treatment for carriers with a new primary can be quickly assessed increasing the likelihood of a positive outcome after early diagnosis for participants, which has been stated as a key benefit for continued screening 22,23 . However, clinical studies of this rigorous screening protocol have reported to have psychosocial drawbacks 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Once identified early, treatment for carriers with a new primary can be quickly assessed increasing the likelihood of a positive outcome after early diagnosis for participants, which has been stated as a key benefit for continued screening 22,23 . However, clinical studies of this rigorous screening protocol have reported to have psychosocial drawbacks 22,23 . Nevertheless, early detection and peace of mind after results disclosure are noted as benefits gained through the screening process that outweigh the drawbacks 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress resulting from undergoing inappropriate surveillance has also been postulated as a justification for caution . However, TP53 mutation carriers participating in surveillance derive psychological benefit . The recent whole‐body MRI data are changing this situation, with the American Association of Cancer Researchers and the US National Comprehensive Cancer Network Guidelines for management of LFS issuing surveillance recommendations that include whole‐body MRI.…”
Section: Surveillance In Hereditary Sarcomamentioning
confidence: 99%